The shape and shaping of the book of Psalms: the current state of scholarship - DeClaissé-Walford, Nancy L. (Ancient Israel and Its Literature, 2014)
Intro -- Contents -- Preface -- Abbreviations -- The Canonical Approach to Scripture and The Editing of the Hebrew Psalter -- The Editing of the Psalter and the Ongoing Use of the Psalms: Gerald Wilson and the Question of Canon -- Changing Our Way of Being Wrong: The Impact of Gerald Wilson's The Editing of the Hebrew Psalter -- The Dynamics of Praise in the Ancient Near East, or Poetry and Politics -- Philosophical Perspectives on Religious Diversity as Emergent Property in the Redaction/Composition of the Psalter -- Let Us Cast Off Their Ropes from Us: The Editorial Significance of the Portrayal of Foreign Nations in Psalms 2 and 149 -- The Message of the Asaphite Collection and Its Role in the Psalter -- Instruction, Performance, and Prayer: The Didactic Function of Psalmic Wisdom -- "Wealth and Riches Are in His House" (Ps 112:3): Acrostic Wisdom Psalms and the Development of Antimaterialism -- Perhaps YHWH Is Sleeping: "Awake" and "Contend" in the Book of Psalms -- Revisiting the Theocratic Agenda of Book 4 of the Psalter for Interpretive Premise -- On Reading Psalms as Liturgy: Psalms 96-99 -- The Role of the Foe in Book 5: Reflections on the Final Composition of the Psalter -- Gerald Wilson and the Characterization of David in Book 5 of the Psalter -- The Contribution of Gerald Wilson toward Understanding the Book of Psalms in Light of the Psalms Scrolls -- Imagining the Future of Psalms Studies -- Contributors -- Index of Ancient Sources -- Index of Modern Authors.